Mise en œuvre d’un modèle d’analyse des raisonnements en classe de mathématiques à l’école primaire - Gibel, Patrick (Éducation et didactique, 2015)
This paper aims at establishing relevance of a model to analyse reasoning processes in problem solving situations. We would like to describe our model of analysis on one hand in order to highlight the main elements which structure the analysis, on the other hand to show his interest to analyse lesson, even in a context further from this one used during his conception.This model, made mainly within the frameworks of the theory of didactical situations and Pierce's semiotic theory, allows to characterize reasoning processes, elaborated by the pupils and the teacher, during situation of action, situation of formulation and also in situation of validation. We will exemplify this model to study reasoning processes elaborated during a lesson, produced by Brousseau, aiming at favouring reasoning process and at revealing the rules of the games of the proof to pupils, in primary school (pupils aged 10 to 11).